Property improvement of TiNi by Cu addition for orthodontics applications - A. Phukaoluan (2018)
This study aims to investigate mechanical properties and transformation behavior of TiNiCu shape memory alloys to obtain optimal conditions for utilizing as orthodontic wires. TiNi binary alloys with Ni-content 50.6 at.%, TiNiCu alloys with Cu-content ranging from 5 to 10 at.%, were prepared. The alloys were melted by electrical arc-melting method and then homogenized at, 800°C for 3600 s. The alloys were subsequently sliced into thin plates (1.5 mm) by EDM wire cutting machine. To evaluate mechanical properties, the specimens were cold-rolled with 10, 20 and, 30%, followed by heat treatment at 400°C and 600°C for 3600 s, respectively. A Differential Scanning Calorimeter (DSC) was used to detect transformation temperatures. Mechanical properties were evaluated by micro hardness and three-point bending tests. The results showed that transformation temperatures were strongly increased with increasing Ni-content. Moreover, the decrease in transformation temperature after increasing level of cold-rolling reduction ratio suggests that internal stress can depress transformation. However, internal stress seemed to support the introduction of superelasticity for each specimen. In addition, specimens heat treated at 400°C have more appropriate properties as orthodontic wires than those heat-treated at 600°C due to the remaining effect of cold-working. These results can be take into consideration for optimizing alloy composition and mechanical properties of TiNiCu shape memory alloys for orthodontics wires purposes. © (2011) Trans Tech Publications.